A Proposal to the National Science Foundation for the Expansion of the Synchrotron Radiation Center of the University of Wisconsin-Madison - Synchrotron Radiation Center Staff (My University, 1976)
Proposal to the National Science Foundation to fund construction of the Aladdin ring at the Synchrotron Radiation Center.
Keywords: Aladdin; Synchrotron